1999
DOI: 10.1002/(sici)1098-0997(1999)7:1/2<10::aid-idog3>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein expression during gametogenesis and embryogenesis

Abstract: When cells are subjected to various stress factors, they increase the production of a group of proteins called heat shock proteins (hsp). Heat shock proteins are highly conserved proteins present in organisms ranging from bacteria to man. Heat shock proteins enable cells to survive adverse environmental conditions by preventing protein denaturation. Thus the physiological and pathological potential of hsps is enormous and has been studied widely over the past two decades. The presence or absence of hsps influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
(16 reference statements)
0
19
0
Order By: Relevance
“…Defects in this gene have been implicated in Marinesco–Sjögren syndrome, which commonly presents with hypogonadism [48]. Heat-shock proteins are important for proper gametogenesis and embryogenesis, and induction of heat-shock protein-related mRNAs in sperm due to environmental stress could benefit the embryo after fertilization [49]. IFT81, also known as CDV-1, is necessary for the assembly and maintenance of eukaryotic cilia and flagella [50].…”
Section: Discussionmentioning
confidence: 99%
“…Defects in this gene have been implicated in Marinesco–Sjögren syndrome, which commonly presents with hypogonadism [48]. Heat-shock proteins are important for proper gametogenesis and embryogenesis, and induction of heat-shock protein-related mRNAs in sperm due to environmental stress could benefit the embryo after fertilization [49]. IFT81, also known as CDV-1, is necessary for the assembly and maintenance of eukaryotic cilia and flagella [50].…”
Section: Discussionmentioning
confidence: 99%
“…As expression pattern analysis showed ( Figure 3 A,B), HSP60 and HSP10 mRNA transcripts were ubiquitously expressed in all tissues examined and with higher expression in gonads. These results indicated that HSP10 and HSP60 were synthesized constitutively to support the basic metabolism and gonads development [ 8 , 28 ]. Moreover, the expression of HSP10 and HSP60 mRNA transcripts was significantly up-regulated during the onset of migration behavior ( Figure 3 C).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that HSP60 and HSP10 are essential for various cellular processes [ 28 ]. In this study, IHC results revealed that there were higher expression levels of HSP60 and HSP10 in the primary spermatogonia, weak or absent expression was seen in the mature germ cells ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins represent a set of highly conserved molecular chaperones that serve by folding newly synthesized proteins, disassembling unstable proteins, and assisting in the transportation of proteins within the cell [28]. They enable cells to survive adverse environmental conditions, and their absence damages the embryonic development in mice [29,30]. Christensen et al show that homozygosity for the null allele of Hspd1 causes early embryonic lethality, while heterozygosity for the inactivated allele permits embryonic development and postnatal survival [30].…”
Section: Discussionmentioning
confidence: 99%